Pola Asuh al-Ummu Madrasat al-Ula dalam Membentuk Karakter Anak Kiai - Selawati, Selawati; Wahyuni, Siti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2022)
This study aims to describe the upbringing of al-Ummu Madrasat al-Ula in shaping the character of the Kiai's sons and daughters in Pesantren. This study uses a type of qualitative research with a case study approach. Data collection techniques using direct observation, in-depth interviews, and documentation. The informants of this study were the Kiai family (dhurriyyah), royal servants, the chairman of pesantren, and the chief editor of the Pesantren Press. This study found that the implementation of parenting al-Ummu Madrasat al-Ula in shaping the character of Kiai's sons and daughters used a combination of authoritarian, democratic, and permissive parenting styles. The blend of parenting styles has implications for forming the positive character of the Kiai's children, such as asking permission, apologizing, asking for help, being sociable, respectful to elders, obedient to parents, and generous likes to share with his friends.